Pediatric multisystem inflammatory syndrome associated with COVID-19 (Research, Society and Development, 2022)
Our study aimed to review the literature on pediatric multisystem inflammatory syndrome associated with COVID-19. This is an integrative literature review carried out through the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Data Bank in Nursing (BDENF) and Medical Literature Analysis and Retrieval System databases. Online (MEDLINE). ), through the following Health Sciences Descriptors (DeCS): “Child”, “Complications” and “COVID-19”. Combined with each other by the rolling AND operator. As inclusion criteria: articles available online, in full, in Portuguese, Spanish and English, that address the theme, in the last three years (2019-2022). As exclusion criteria: articles that do not contemplate the subject and studies repeated in the databases. After the joint search for descriptors and operators, 3,074 articles on the topic emerged, applying the exclusion and inclusion criteria, 249 articles were found, 8 articles selected to compose the final sample. In view of the exposure, we can see that the pediatric multisystem inflammatory syndrome affects most children regardless of vaccination or especially in the new variants, and may even be an adverse event secondary to vaccination.